Systemic Arterial Blood Pressure and Intracerebral Hemorrhage after Mechanical Thrombectomy in Anterior Cerebral Circulation. (June 2021) - An, Jiaqi; Tang, Yonglan; Cao, Xiangqi; Yuan, Huijie; Wei, Meng; Yuan, Xingyun; Zhang, Aifeng; Li, Yongxin; Saguner, Ardan; Li, Guoliang; Luo, Guogang
The relationship between systemic arterial blood pressure (BP) and intracerebral hemorrhage (ICH) after mechanical thrombectomy (MT) of the cerebral artery remains unclear. This study aimed to determine the effect of BP variables on ICH after MT in patients with acute occlusions of the anterior cerebral circulation. Patients undergoing MT due to acute occlusions of the anterior cerebral circulation were enrolled in this single-center study. Non-invasive BP data following MT were obtained within the first 24 hours, including mean, maximum, minimum, difference between maximum and minimum, SD and coefficient of variation for systolic BP (SBP) and diastolic BP (DBP) and mean arterial pressure. ICH was defined and classified according to the European Cooperative Acute Stroke Study-II. In 164 enrolled patients (median age 65 (IQR 56-75) years; 31.7% female), higher maximum (89.5 mm Hg vs 98.5 mm Hg, p=0.001) and SD (9.8 mm Hg vs 10.9 mm Hg, p=0.038) of DBP were associated with higher risk of ICH. The optimal cut-off values associated with ICH for maximum SBP were 155 mm Hg and for maximum DBP 92.5 mm Hg, respectively. Higher BP within 24 hours after MT in acute occlusions of the anterior cerebral circulation is associated with a greater risk of ICH. More studies are needed to further determine optimal BP goals in the acute phase after MT.